The Topic of Youth in Czech Prose of 1960s Exampled on the Stories by Jan Beneš - Zemanová, Zuzana (Bohemica Olomucensia, 2016)
The paper is concerned with the topic of youth in Czech prose in 1960s, especially in books of short stories by Jan Beneš: Do vrabců jako když střelí (1963), Situace (1963) and Disproporce (1969). While most authors of the previous decade focused on young persons from the society's point of view, at the end of 1950s their attention shifted to young person's inner world and emotional life and this tendency further intensified in 1960s. Jan Beneš focuses on the life of young generation in social and emotional aspects, their leisure activities, interests, etc. He also deals with taboo problems like prison camps of communist regime or relations to old people.
Keywords: Czech prose; 1960s; Jan Beneš; youth